PENGARUH PEMBERIAN KACANG EDAMAME (Glycin max (L)merrill)TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI KLINIK FITRI ASIH KECAMATAN PATUMBAK KABUPATEN DELI SERDANG TAHUN 2022 - Siagian, Nurul Aini; Siregar, Devi Linda SM (Jurnal Penelitian Keperawatan Medik, 2023)
Background Back : bosom milk is food normal first _ for child . Absence of milk creation brings about work on breastfeeding for children no satisfied . Method Research : Review this utilization Quasy Investigation Plan ( Configuration Examination pseudo ) with use plan one Gathering Pre test - Post test Plan . Populace in concentrate on this that is entire post pregnancy 10 individuals and an example of 10 individuals. Concentrate on this utilizing the all out examining method with examination univariate and bivariate . The exploration results acquired from information investigation with Wilcoxon 's test demonstrated the way that post pregnancy moms can finished up gift nut soya bean youthful ( edamame beans ) pre-test and post-test. Brings about table is known that score P - esteem (0.007) < 0.05 then H0 is dismissed Ha is acknowledged which implies there is the impact of pre-test and post-test on giving nut soya bean youthful ( edamame beans ) against bosom milk creation in post pregnancy moms at the Center Fitri love Subdistrict Patumbak Store Serdang Regime . Conclusion : in concentrate on this showing results that there is impact nut soya bean youthful ( edamame beans ) against bosom milk creation in post pregnancy moms . Idea: it is trusted that the facility will give data on mother bosom feed in increment milk creation can drink nut soybeans